Sinonasal tubulopapillary low-grade adenocarcinoma. Histopathological, immunohistochemical and ultrastructural features of poorly recognised entity - Skalova, A; Cardesa, A; Leivo, I; Pfaltz, M; Ryska, A; Simpson, R; Michal, M (Virchows Archiv, 2003)
We present the clinicopathological, histological and immunohistochemical findings of six cases of primary tubulopapillary low-grade adenocarcinoma of the sinonasal tract with ultrastructural examination in one case. Due to its unique features, we believe that primary tubulopapillary low-grade adenocarcinoma of the sinonasal tract represents a tumour entity different from any tumours generally recognised in the sinonasal region. Our cases had an equal sex incidence, with an age range of 44-76 years. The tumour has a tendency to recur, but none of our six patients developed metastases. We feel that it is important to separate this tumour entity from other types of sinonasal adenocarcinomas that exhibit a papillary growth pattern, as they frequently pursue a much more aggressive clinical course than the tumours in this study.
Keywords: dospělí; Female; organely; Organelles; Adult; nádory vedlejších dutin nosních; výsledek terapie; ženské pohlaví; Microscopy, Electron; lidé; Cell Nucleus; Adenocarcinoma, Papillary; Microvilli; Treatment Outcome; elektronová mikroskopie; imunoenzymatické techniky; buněčné jádro; Adenocarcinoma; Male; nádorové biomarkery; Aged; adenokarcinom; mikroklky; papilární adenokarcinom; Paranasal Sinus Neoplasms; Immunoenzyme Techniques; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans